Cost-effective and green approach for the synthesis of zinc ferrite nanoparticles using Aegle Marmelos extract as a fuel: catalytic, electrochemical, and microbial applications - Lakshmi Ranganatha, V.; Pramila, S.; Nagaraju, G.; Udayabhanu; Surendra, B. S.; Mallikarjunaswamy, C. (Journal of materials science. Materials in electronics, 2020)
Today, due to industrialization and urbanization, the world is facing serious water shortage and environmental alarms. The reusability of polluted water could be a promising approach for the sustainable wastewater management strategy. In the view, the present work compiles the synthesis of zinc ferrite (ZnFe 2 O 4 ) nanoparticles by a simple, economic, and eco-friendly route. The investigation of structural properties, thermal properties, and optical properties was carried out successfully by standard characterization techniques. The X-ray diffraction patterns confirmed the spinel-cubic lattice with Fd-3m space group for all the samples. The presence of vibrational frequency modes of Zn–O and Fe–O was ensured by FTIR spectra. The nano-size, morphology, atomic percentage, and some agglomeration of the nanoparticles were revealed by SEM–EDX and TEM images. The bandgap values were calculated from UV–Visible analysis data, and found to be 2.36 eV. The distribution of pore size by BJH method and BET surface area was evaluated by Nitrogen adsorption–desorption isotherms, and is found to be 19.74 m 2 /g. The thermogravimetric and differential thermal analysis affirmed percentage of weight loss and phase formation. The photocatalytic activity of methylene blue was evaluated under visible light and the removal efficiency of 96% and nano-catalyst shows active reusability. The cyclic voltammetry and electrochemical impedance spectroscopy (EIS) were used for the study of electrochemical properties of nanoparticles. Further, the antimicrobial activity of the nanoparticles was investigated using Gram-positive, Gram-negative bacteria and some selected fungi strains. The obtained results revealed that the newly synthesized ZnFe 2 O 4 can act as potential photocatalyst, electrochemical sensor, and antimicrobial agent.